Analysis of the Application of the Hedonic Price Method in Setting House Rental Prices in the Coastal Area of Padang City - Putri, Aulia; Tri Kurniawati (Jurnal Economic Resource, 2025)
This research investigates how structural, location, and environmental attributes impact residential rental rates in Padang City, a region challenges by disaster risks and limited facility access. The study aims to identify key determinants affecting rental costs. A quantitative research design was employed, utilizing questionnaires for data collection, followed by analysis through multiple linear regression. Finding reveal that all three independent variables significantly affect rental pricing, as reflected by an F-value of 61,607, substantially surpassing the critical threshold of 2,69. These insights are valuable for shaping more effective housing policy strategies.